2020
DOI: 10.1109/tnsre.2020.2984809
|View full text |Cite
|
Sign up to set email alerts
|

Portable Gait Lab: Estimating 3D GRF Using a Pelvis IMU in a Foot IMU Defined Frame

Abstract: Ground Reaction Forces (GRF) during gait are measured using expensive laboratory setups such as in-floor or treadmill force plates. Ambulatory measurement of GRF using wearables enables remote monitoring of gait and balance. Here, we propose using an Inertial Measurement Unit (IMU) mounted on the pelvis to estimate the GRF during gait in daily life. Calibration procedures and an Error State Extended Kalman filter (EEKF) were used to transform the accelerations at the center of mass (CoM) to the 3D GRF. The ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 29 publications
0
55
2
Order By: Relevance
“…In order to facilitate MIMU-based segmental analysis in the clinical field, it is essential to keep the number of required sensors as low as possible while achieving sufficient accuracy [ 14 , 17 ]. Therefore, similarly to what is done with OMCSs, the sacral method paradigm, consisting of using a single sensor positioned on the lower back, has been widely investigated [ 34 , 35 , 36 , 37 , 38 , 39 ]. While this approach is quick and easy to implement, it was shown to lack accuracy when dynamical motion of the upper body was involved [ 2 , 37 , 39 ] or in case of asymmetrical gait pattern [ 15 , 35 ], such as for people with lower-limb amputation [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate MIMU-based segmental analysis in the clinical field, it is essential to keep the number of required sensors as low as possible while achieving sufficient accuracy [ 14 , 17 ]. Therefore, similarly to what is done with OMCSs, the sacral method paradigm, consisting of using a single sensor positioned on the lower back, has been widely investigated [ 34 , 35 , 36 , 37 , 38 , 39 ]. While this approach is quick and easy to implement, it was shown to lack accuracy when dynamical motion of the upper body was involved [ 2 , 37 , 39 ] or in case of asymmetrical gait pattern [ 15 , 35 ], such as for people with lower-limb amputation [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…IMUs have recently become even more reliable as several methods to estimate GRFs using IMUs have been developed [9,10,[18][19][20][21][22]. A recent study analyzed the feasibility of using an IMU mounted underneath the walking surface and measured comparable accuracy to IMUs attached to the body [18].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting trend is the addition of machine learning methods to estimate GRFs using IMUs. Most of the studies that have been previously discussed use machine learning methods to estimate GRFs with the use of IMUs [9,10,[19][20][21][22]. These studies have demonstrated promising results when estimating vertical and three-dimensional GRFs.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve better performance, one may leverage long-term recordings by averaging out cycle-to-cycle variation in estimation errors over many gait cycles, or use additional sensing modalities, preferably packaged such that the number of sensor units will not increase. For example, distance ranging measurements or pressure insoles can be used to infer position of the pelvis [11,43]. Attaching cameras to the body is another interesting approach (e.g., Xu et al tracked body pose using cap-mounted fisheye cameras pointing downwards [44]; using cameras with IMUs for better position estimation [45]).…”
Section: Towards Monitoring Activities Of Daily Living (Adl)mentioning
confidence: 99%